Glutathione capped inverted core-shell quantum dots as an efficient photocatalyst for degradation of organic dyes. (February 2020) - Bhuvaneswari, K.; Vaitheeswari, V.; Palanisamy, G.; Maiyalagan, T.; Pazhanivel, T.
Abstract: Herein, we focused on the preparation of Glutathione (GHS) capped ZnS, CdS and inverted type-I ZnS@CdS core-shell quantum dots (QDs) through reflux condensation method. The XRD and HR-TEM analysis confirms the formation of core-shell QDs with corresponding crystal structures. The optical properties and band energy of the as prepared samples were evaluated from optical absorption study. The blue shift of absorption was observed in the core-shell QDs system which may be due to the quantum size effect. The EDX and elemental mapping study confirm the existence of Zn, Cd and S elements in the as-prepared material. When compared to ZnS and CdS QDs, the as prepared ZnS@CdS QDs shows improved photocatalytic activity toward the MB dye degradation due to the effective separation of the photogenerated electron-hole pair. The inverted ZnS@CdS core-shell structure not only enhances the light absorption also to reduce the charge recombination of the photocatalysts for the effective charge and energy transfer between the components during degradation. Finally, the scavenging activity and reusability of the ZnS@CdS core-shell QDs samples were examined under UV–Vis. Light irradiation. Graphical abstract: Image 1 Highlights: Inverted type-I ZnS@CdS core-shell QDs photocatalyst was prepared over reflux condensation method. The preparation of inverted type-I ZnS@CdS QDs structure gives improved photocatalytic activity towards MB dye owing to its intermediate band structure and effective charge separation of photogenerated charge carriers. The as prepared catalyst shows better photocatalytic activity against MB dye due to the effective charge carriers separation.